Impact of global cotton markets on rural poverty in Benin - Minot, Nicholas; Daniels, Lisa (Wiley, 2005)
World cotton prices fell by about 40% over 2001–2002, focusing attention on the effect of subsidies for cotton growers in depressing world prices. This paper combines farm survey data from Benin with assumptions about the decline in farm‐level prices to estimate the direct and indirect effects of cotton price reductions on rural income and poverty in Benin. The results indicate that there is a strong link between cotton prices and rural welfare in Benin. A 40% reduction in farm‐level prices of cotton results in an increase in rural poverty of 8% points in the short run and 6–7% points in the long run. Under the assumptions of the partial input‐output model, we estimate the multiplier to be in the range of 2.96, meaning that 1 US$ of reduced income by cotton growers results in a contraction of 2.96 US$ in overall income. Finally, econometric analysis of the determinants of the demand for hired agricultural labor suggests that falling cotton prices will not greatly reduce labor demand since the labor intensity of cotton is similar to that of competing crops in Benin. Overall, the study demonstrates the impact of changes in world cotton prices on rural poverty in Benin, thus highlighting the likely negative effects of cotton subsidies in the United States and elsewhere on Benin farmers.